Making great strategy : arguing for organizational advantage - Carroll, Glenn R. (Columbia Business School Publishing, 2020)
Making strategy requires undertaking major'often irreversible'decisions aimed at long-term success in an uncertain future. All leaders must formulate a clear course of action, yet many lack confidence in their ability to think systematically about their strategy. They struggle to apply the abstract lessons offered by conventional approaches to strategic analysis to their unique contexts.Making Great Strategy resolves these challenges with a straightforward, readily applicable framework. Jesper B. S'rensen and Glenn R. Carroll show that one factor underlies all sustainably successful strategies: a logically coherent argument that connects resources, capabilities, and environmental conditions to desired outcomes. They introduce a system for formulating and managing strategy through a set of three core activities: visualization, formalization and logic, and constructive argumentation. These activities can be implemented in any organization and are illustrated through examples and case studies from well-known companies such as Apple, Walmart, and The Economist.This book shows that while great strategic thinking is hard, it is not a mystery. Widely applicable and relevant for managers and leaders at all levels, especially executive teams charged with setting the course of their organizations, it is essential reading for anyone faced with practical problems of strategic management.